Study of maternal and foetal outcome in COVID-19 anaemic patients during COVID pandemic in a tertiary centre - Chavan, Niranjan; Ammara, Umme; Kapote, Deepali; Deshmukh, Prasad; Sakhalkar, Ashwini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The haemoglobin concentration is one of the most critical indicators of the blood’s oxygen-carrying ability. Due to the hypermetabolic condition produced by infection, anaemia in COVID-19 positive pregnant women might result in tissue hypoxia due to increased peripheral tissue oxygen demands. Complications such as multi-organ failure and acute respiratory distress syndrome can worsen the prognosis. Since hemoglobin is necessary for tissue oxygenation, anaemia may have a substantial impact on the prognosis of COVID-19 pneumonia, where tissue hypoxia develops as a result of disease pathogenesis. Aim of the current study was to study the effect of COVID-19 on pregnant women with anaemia in pregnancy, including symptoms and foetomaternal outcome in patients admitted to a tertiary care facility. Methods: Observational study done on pregnant females in labour and post-delivery patients who were diagnosed with COVID-19 infection using the SARS COV-2 nasopharyngeal reverse transcriptase polymerase chain reaction (RT-PCR) from 1st April 2020 to 30th June 2021. The required demographic, clinical details and haemoglobin levels were obtained, and selected participants were followed up until they were discharged. Results: In our study, out of 58 women, who had anaemia in pregnancy with COVID-19 infection delivering 59 neonates (1set of twins), 55.5% were in the age group of 25-35 years, 77% reached full term pregnancy and 67% were multigravida. 51.7 % patients were transferred from periphery hospitals. Delivery was by caesarean section in 61% and 39% delivered vaginally. 38.8% neonates delivered had birthweight of <2.5 kg out of which 20% had intrauterine growth restriction and 22.4 % were preterm. 3.4% stillbirth were reported. No maternal deaths were reported. Conclusions: From our study, maternal and neonatal outcome were unaffected by anaemia in COVID-19 pregnant women. Severely anaemic patients with comorbidities should be transferred to centres with appropriate neonatal intensive care facilities for delivery.